Ecological, Biological and Hematological Index of the Blood Analysis of Sturgeons (Acipenser) in the Caspian Sea - Abdulaeva , Naid; Alieva, Saniyat (KnE Life Sciences, 2021)
The Caspian is a unique drainless water body with no connection to the ocean. This study of the peculiarities of blood cell composition of the Russian sturgeon (Acipenser güldenstädtii) and sevruga (Acipenser stellatus) revealed minor destructive disorders of the blood cells. The number of blood cells also deviated from conditional norms. The study of the leukocyte profile of sturgeons showed the granular forms of leukocytes, band neutrophils and eosinophils, and segmentonuclear neutrophils and eosinophils. The total number of granulocytes in the blood of the Russian sturgeon was increased, which indicated the activation of the body’s protective systems in response to the anthropogenic load. In cytomorphological terms, the destructive disorders were revealed. Such phenomena are associated with the ever-increasing anthropogenic load on the biocenoses of natural reservoirs. Summarizing the results, it can be concluded that the quantitative indicators of red blood in the Russian sturgeon (Acipenser gueldenstaedtii) and sevruga (Acipenser stellatus) caught off of the Dagestan coast of the Caspian Sea were reduced in the spring of 2018 compared to 2016, but were in the normal range given in the literature. The concentration of hemoglobin in the Russian sturgeon and sevruga in 2016 was 13% and 15% higher than in 2014, respectively. This phenomenon could be a measure to compensate for the lack of oxygen in various fish tissues and organs. Keywords: Russian sturgeon, red blood cells, lymphocytes, eosinophils, neutrophils, anisocytosis, cytolysis of red blood cells